ON THE STABILITY OF TWO-DIMENSIONAL DISCRETE-SYSTEMS - COMMENT - BOLAND, FRANCIS MORGAN (ISI Web of Science, 1981)
This correspondence shows that independent necessary conditions and sufficient conditions for the asymptotic stability of two-dimensional discrete linear systems presented by Ahmed can be readily obtained from previous results.
PUBLISHED
Keywords: TWO-DIMENSIONAL DISCRETE-SYSTEMS